Dihydroarteannuin Ameliorates Collagen-Induced Arthritis Via Inhibiting B Cell Activation by Activating the FcγRIIb/Lyn/SHP-1 Pathway - Congqi Hu; Congqi Hu; Danbin Wu; Danbin Wu; Jiahui Yu; Jiahui Yu; Jia Xu; Jia Xu; Lijuan Liu; Lijuan Liu; Mingying Zhang; Mingying Zhang; et al. (Frontiers Media S.A., 2022)
Background: Dihydroarteannuin (DHA), which is extracted from the traditional Chinese herb Artemisia annua L, exhibits potent immunosuppressive activity in rheumatoid arthritis (RA). Strong evidence indicates that B cells act as an essential factor in the pathogenesis of RA, but research on the immunosuppressive function of DHA in regulating B cells is limited.Objective: To investigate the modulatory effects of DHA on joint destruction, proinflammatory cytokine production, activation, apoptosis and proliferation of B cells and to explore the possible associated mechanism in RA treatment.Methods: Collagen-induced arthritis (CIA) model was established. Weight and joint oedema were record weekly, and joint damage was detected by micro-CT scan. Human Burkitt B lymphoma cells lacking endogenous Fc gamma receptor b (FcγRIIb) gene were transfected with a 232Thr loss-of-function mutant to construct a mutant cell model ST486. The proliferation of ST486 cells was assessed with Cell Counting Kit-8. Apoptosis and activation were tested by flow cytometry. The effects of DHA on the activation of FcγRIIb, protein tyrosine kinases (Lyn), and SH2-containing tyrosine phosphatase-1 (SHP-1) signaling pathways were determined by western blotting.Results: In comparison to model group, bone volume/tissue volume (BV/TV) and bone mineral density (BMD) were increased, whereas joint oedema was decreased in both of the DHA and MTX group. The mRNA and protein expression levels of Interleukin-6 (IL-6) and Tumor necrosis factor-alpha (TNF-α) were decreased after treatment with DHA. In addition, DHA treatment promoted the apoptosis, inhibited the activation and proliferation of ST486 cells. Furthermore, the protein expression levels of FcγRIIb, SHP-1, and Lyn were increased after treatment with DHA. Moreover, the expression of phosphorylated CD19 was also inhibited by DHA.Conclusion: We provide the first evidence that DHA may alleviate collagen-induced arthritis by activating the FcγRIIb/Lyn/SHP-1 signaling pathway in B cell, indicating that DHA is a novel and valuable candidate for RA therapy.